Methods for selecting the best partner construction enterprise in terms of partnering relations - Radziszewska-Zielina, Elżbieta (Journal of Civil Engineering and Management, 2010)
The author proposes fourteen parameters for assessing partnering relations in construction enterprises. By means of these parameters, experts in construction enterprises apply a five‐point scale in order to evaluate enterprise relations with four transactors within its microenvironment. The parameters describing relationships are adopted as assessment criteria. The question of selecting the best construction enterprise for cooperation is a multi‐criteria issue. The author's solution is based on the ELECTRE III method and elaborates two alternative methods of selecting the best construction enterprise on the basis of the analysis of partnering relations between construction enterprises being studied and their transactors within the microenvironment and indicates one of the above introduced methods as preference. Two methods have been developed with a view to supporting a decision‐making system in a construction enterprise as regards the choice of a subcontractor. Relevant calculations can be made by the enterprise decision‐maker using the ConRel programme elaborated by the Cracow University of Technology.First Published Online: 10 Feb 2011